Calculating the Muon cooling within a MICE solid and liquid absorber - Yang, S; Green, M; Virostek, S (European Physical Society Accelerator Group (EPS-AG), 2006)
The key elements of the Muon Ionization Cooling Experiment (MICE) [1] cooling channel are the absorbers that are a part of the MICE absorber focus coil modules (AFC modules). The boundaries of room temperature solid absorbers are well defined. The density of most solid absorber materials is also well understood. The properties of solid absorber are most certainly understood to 0.3 percent. The MICE liquid absorbers are different in that their dimensions are a function of the absorber temperature and the fluid pressure within the absorber. The second element in the liquid absorber is the variability of the liquid density with temperature and pressure. While one can determine the absorber boundary within 0.3 percent, the determination of the liquid density within 0.3 percent is more difficult (particularly with liquid helium in the absorber). This report presents a method of calculating absorber boundary and the cooling performance of the MICE absorbers as a function of fluid temperature and pressure.